2004
DOI: 10.17221/3407-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Gel strength of the native egg white

Abstract: The study examined gel strength of the native egg white as a function of pH and the dry matter content. The egg white samples were isolated from fresh eggs and the eggs in different stages of storage. The gel strength was measured with Texture Analyser of TA-XT2i type. The study has shown that the gel strength increases with rising pH and the content of dry matter. The influence of the egg age is more complicated. The gel strength increases over the first 14 days after egg laying and slowly decreases afterward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…At the end of the experiment, 24 eggs (4 egg per replicate) were randomly collected from each treatment for the gelling properties determination according to the previous method (Houska et al, 2004 ). Briefly, surface of the egg was wiped with alcohol cotton, albumen and egg yolk were separated, albumen was kept in 100 mL beaker, and mixed with a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, 24 eggs (4 egg per replicate) were randomly collected from each treatment for the gelling properties determination according to the previous method (Houska et al, 2004 ). Briefly, surface of the egg was wiped with alcohol cotton, albumen and egg yolk were separated, albumen was kept in 100 mL beaker, and mixed with a magnetic stirrer.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in structure of egg protein lead to coagulate the egg protein (Tan et al, 2012). According to Houška et al (2004), egg white gel strength increased with the egg white concentration. Hence the highest gel strength in fresh duck eggs can be due to high amount of albumin present especially when compared with chicken egg (Jalaludeen & Chutchil, 2006).…”
Section: Comparison Of Village Chicken Shaver Brown Duck Turkey Anmentioning
confidence: 99%
“…Gel strength increased with increasing pH, and the highest gel strength for duck albumen was observed at pH 9 by Ren et al (2010), while at a low pH (pH \ 6), the resulting gels were more brittle but firmer with poor waterbinding properties and low elasticity. Houska et al (2004) investigated the effects of dry matter content and pH on the gel strength of native albumen and the gel strength was found to increase with increasing pH and dry matter content. Raikos et al (2007) also reported that a higher gel strength was found among egg samples at pH 5 and 8 than at pH 2.…”
Section: Gelling Propertymentioning
confidence: 99%